Influence of Regular Statin Intake on Prostate‐Specific Antigen Values, Prostate Cancer Incidence and Overall Survival in a Prospective Screening Trial (ERSPC Aarau) - Alkiviadis Papagiannakis; Maciej Kwiatkowski; Stephen F. Wyler; Ashkan Mortezavi; Lukas Manka; Marian S. Wettstein; Rainer Grobholz; Angelika Hammerer‐Lercher; Daniel Eberli; Lukas Werner Prause (Cancer Medicine)
ABSTRACT Objective While statins have demonstrated a variety of antineoplastic effects in preclinical studies, several retrospective clinical studies and observational studies have not shown a consistent chemopreventive benefit against prostate cancer (PCa). Therefore, in this population‐based cohort study, we examined the association of statin intake on prostate specific antigen (PSA) values and risk of development of PCa. Method N = 4,314 men from the Swiss section of the European Randomized Study of Screening for Prostate Cancer (ERSPC) were evaluated. N = 761 men were statin users [Stat+]. The median follow‐up was 9.6 years. A transrectal prostate biopsy was performed in men with a PSA‐level ≥ 3 ng/mL. Mortality and incidence data was obtained through registry linkages. PCa incidence, total serum PSA level, free‐to‐total PSA level, and overall survival were compared between [Stat+] and [Stat−] patients. Results Total PSA values were significantly lower in [Stat+] patients at baseline (1.5 vs. 1.8 ng/mL, p < 0.001) and at last follow‐up (1.8 vs. 2.1 ng/mL, p < 0.001). PCa detection during the follow‐up period was significantly associated with baseline PSA. The overall incidence of PCa showed no statistical difference among [Stat+] and [Stat−] groups (7.4% vs. 9.5%, p = 0.08), indicating that statin use had no effect on the risk of developing PCa during follow‐up. [Stat+] patients had a significantly higher overall mortality risk compared to [Stat−] patients (HR 2.04, p < 0.001). Discussion A significant risk reduction in the development of PCa in [Stat+] patients was not found. We did observe lower PSA values among [Stat+] patients, compared to [Stat−] patients, with an increasing difference during follow‐up.